Meta Analysis the Effect of Intervention Based School toward Nutrition on Body Mass Index - Wulandari Wulandari; Yulia Lanti Retno Dewi; Bhisma Murti (Masters Program in Public Health, 2021)
Background: Body mass index (BMI) is a metric used to define anthropometric characte